2017
DOI: 10.1007/s00381-016-3332-7
|View full text |Cite
|
Sign up to set email alerts
|

Children presenting in delayed fashion after minor head trauma with scalp swelling: do they require further workup?

Abstract: Pediatric patients ≤24 months of age presenting to the ER in delayed fashion with scalp swelling after minor head trauma-who were otherwise nonfocal on examination-did not require surgical intervention and did not experience any neurologic decline. Further radiographic investigation did not alter neurosurgical management in these patients; however, it should be noted that workup for child abuse and social care may have been influenced by CT findings, suggesting the need for the future development of a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
4
10
0
Order By: Relevance
“…All of Sellin et al . 's patients had a CT head, and they describe isolated linear/non‐displaced skull fractures in 33 of 78 (42%) of patients, linear/non‐displaced skull fractures with associated extra‐axial haemorrhage (epidural or subdural hematoma) in 32 of 78 (41%) and a normal CT head in 4 of 78 (5.1%) . These results are almost identical to our results, and the higher rate of skull fracture in this and our study is probably related to the population group, that is, patients presenting with a scalp haematoma more than 24 h after injury may be more likely to have an underlying skull fracture.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…All of Sellin et al . 's patients had a CT head, and they describe isolated linear/non‐displaced skull fractures in 33 of 78 (42%) of patients, linear/non‐displaced skull fractures with associated extra‐axial haemorrhage (epidural or subdural hematoma) in 32 of 78 (41%) and a normal CT head in 4 of 78 (5.1%) . These results are almost identical to our results, and the higher rate of skull fracture in this and our study is probably related to the population group, that is, patients presenting with a scalp haematoma more than 24 h after injury may be more likely to have an underlying skull fracture.…”
Section: Discussionsupporting
confidence: 87%
“…of 76 patients over 2 years, reviewing children younger than 24 months old who presented more than 24 h after injury with scalp swelling after minor head trauma. No patients in that study required neurosurgical intervention or experienced a neurological decline or alteration in neurosurgical management from CT imaging …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delays in seeking medical care for infants and toddlers with skull fractures and STS have been reported, varying from 6.7% to 17.4% of children. 7,8 However, the duration and nature of the delays remain undocumented.…”
mentioning
confidence: 99%
“…Delay in care for children with simple and complex skull fractures, listed as n (%) Sellin, et al found that 41% of children presenting to the emergency department for isolated scalp swelling more than 24 h after injury had an isolated skull fracture and 42% had both a skull fracture and intracranial haemorrhage, but none required intervention 8. Both studies confirm our results that delayed presentations are common for well appearing children with skull fractures presenting to the emergency department for isolated scalp swelling.…”
mentioning
confidence: 99%